Biophotonics Congress: Biomedical Optics 2020 (Translational, Microscopy, OCT, OTS, BRAIN) 2020
DOI: 10.1364/translational.2020.jth2a.7
|View full text |Cite
|
Sign up to set email alerts
|

Compression-induced hemodynamic features of tumors in breast cancer patients undergoing neoadjuvant therapy: a longitudinal case study

Abstract: A dynamic diffuse optical tomographic system, in conjunction with digital breast tomosynthesis, is used to study the hemodynamics in breast tissue under full and partial mammographic compression to evaluate tumor response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Currently, the standard of care for breast cancer screening is X-ray mammography, but optical imaging could complement this method by noninvasively improving contrast. Recently, various optical breast cancer screening methods have been introduced, and several articles have detailed the impact of breast compression on breast hemodynamics, which may be leveraged as a source of contrast for optical mammography modalities and could further open the door for optical detection and/or monitoring of breast tumors [3,4,5,6]. These studies found that, when compression was applied to the breast, considerable differences appeared in the hemodynamic behavior of tumor tissue and healthy tissue, with tumor tissue displaying a decrease in total hemoglobin (HbT) in the range of 2 -20 µM [3,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the standard of care for breast cancer screening is X-ray mammography, but optical imaging could complement this method by noninvasively improving contrast. Recently, various optical breast cancer screening methods have been introduced, and several articles have detailed the impact of breast compression on breast hemodynamics, which may be leveraged as a source of contrast for optical mammography modalities and could further open the door for optical detection and/or monitoring of breast tumors [3,4,5,6]. These studies found that, when compression was applied to the breast, considerable differences appeared in the hemodynamic behavior of tumor tissue and healthy tissue, with tumor tissue displaying a decrease in total hemoglobin (HbT) in the range of 2 -20 µM [3,4,7].…”
Section: Introductionmentioning
confidence: 99%